Spatial distribution and determinants of tetanus toxoid immunization among pregnant women in Ethiopia using data from Ethiopian demographic and health survey 2016 - Beletech Fentie; Tewodros Getaneh Alemu; Masresha Asmare Techane; Chalachew Adugna Wubneh; Nega Tezera Assimamaw; Getaneh Mulualem Belay; Tadesse Tarik Tamir; Addis Bilal Muhye; Destaye Guadie Kassie; Amare Wondim; Bewuketu Terefe; Bethelihem Tigabu Tarekegn; et al. (BMC, 2023)
Abstract Introduction Tetanus is a major public health problem caused by clostridium tetani. Although it is vaccine-preventable, the case fatality rate among neonates in areas with poor immunization coverage and limited access to clean deliveries reaches 80-100%. Vaccination of pregnant mothers with the tetanus toxoid (TT) vaccine is the most effective way to protect against neonatal tetanus. This study aimed to examine the spatial distribution and determinants of tetanus toxoid immunization among pregnant mothers using the 2016 EDHS data. Method Secondary analysis of the Ethiopia Demographic and Health Survey 2016 was done to assess the spatial distribution and determinants of tetanus toxoid vaccine among pregnant women in Ethiopia. Spatial autocorrelation analysis and hot spot analysis were used to detect spatial dependency and spatial clustering of the tetanus toxoid vaccine in Ethiopia. Spatial interpolation was used to predict the tetanus toxoid vaccine coverage in unsampled areas. The multilevel binary logistic regression model was fitted to identify factors associated with tetanus toxoid vaccination. An adjusted odds ratio with 95% CI was calculated and used as the measure of association and a p-value less than 0.05 were considered statistically significant. Result From the total of 7043 pregnant women, 42.4% of them have taken at least two doses of tetanus toxoid immunization. Spatial clustering of TT immunization was observed in the Northern, Southwestern and Southwestern parts of Ethiopia. Whereas, low TT coverage was observed in the Eastern and Western parts of the country. Increased ANC visits and the richest economic status favored TT immunization, whereas living in Addis Ababa and Dire Dewa cities decreased the TT immunization coverage. Conclusion The finding of this study reveals that TT immunization had spatial dependency, with the highest immunization coverage observed in the Northern, Southwestern and Southeastern parts of the Country. Thus, geographically targeted interventions should be implemented particularly in the eastern and western parts of the country.